A modified layered-section method for responses of fire-damaged reinforced concrete beams under static and blast loads. Issue 4 (December 2016) - Pan, Lu; Chen, Li; Fang, Qin; Zhai, Chaochen; Pan, Teng
Reinforced concrete structures are currently under the threat of both fire and blast. The absence of theoretical methods demonstrates a drawback in the assessment of blast-resistant structures after exposure to fire. A modified layered-section method was developed in this article, which was not only able to determine the complete static resistance–deflection curves of fire-damaged reinforced concrete beams but also able to predict the responses of reinforced concrete beams subjected to blast after fire exposure. The high-temperature effects and the strain-rate effects were included in the concrete and steel material models in the proposed method. A corresponding calculation program FBBA was also compiled based on the explicit Newmark algorithm on the platform of Maple software. The developed method and program were validated by the existing test results. Analytical results showed that after fire exposure, the reinforced concrete beams show significant degradation in the residual bearing capacity, but increase in the ductility. The higher the steel reinforcement ratio, the more degradation the bearing capacity of reinforced concrete beams after fire exposure suffers. The blast resistance of the fired reinforced concrete beams was underestimated without considering the strain-rate effects or just considering the average strain-rate effects.